An Overview of Postgraduate Education in Latin America and Other Countries of the World - Vidal Castillo Olivares (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The globalization of academic training, the development of transversal competencies in the different countries of the world, the diversification and expansion of graduate programs in Latin America, the Caribbean and other regions of the world, reflect the academic movement of graduate students in the different universities. Postgraduate training programs are instruments of the policy of the states of each country and through this purpose universities train specialized professionals of high academic level in the different faculties and academic schools that offer quality education in Latin America and the Caribbean, pointing out some of them in Brazil, Colombia, Argentina, Chile, Peru, etc. In Peru, postgraduate education has undergone some changes with respect to the framework of the new university law N° 30220, Chapter 5, on the academic organization in art. 43, on postgraduate studies with specializations, postgraduate diplomas, specialization masters and research or academic masters, and doctorates. Each university establishes the duration of postgraduate studies and the credits or weights of the subject and these are established according to the university law and its regulations. Private universities are also subject to the governing body, who must authorize the National Superintendence of University Education (SUNEDU) to control and supervise the normal development and operation of such educational institution. This overview to the postgraduate studies in the countries of Europe and Asia, in comparison with Latin America and the Caribbean, the academic level of the professional training of the postgraduate studies in these continents such as Europe and Asia are of the highest level, likewise they grant scholarships to Latin Americans to improve and specialize in masters and doctorates in various universities in Europe and Asia, where there are more than 14 countries that grant scholarships to make postgraduate studies in different specialties, then postgraduate studies (masters, doctorate and specializations) are increasingly strengthened in the scientific and technological research of university education in Latin America, the Caribbean and other regions of the world.